A3- and A2B-nitrocorroles: synthesis and antiviral activity evaluation against human cytomegalovirus infection. Issue 7 (19th May 2020) - Bucher, Léo; Kappler-Gratias, Sandrine; Desbois, Nicolas; Bystricky, Kerstin; Gallardo, Franck; Gros, Claude P.
Abstract : We report the 2nd generation of seventeen A2 B- and A3 -substituted fluoronitrocorroles and the discovery of optimized compounds with a selectivity index of >200 against hCMV. Abstract : Human cytomegalovirus (hCMV) is responsible for several pathologies impacting immunocompromised patients and can trigger life-threatening infection. Several antivirals are available and are used in the clinic, but hCMV resistant strains have appeared and patients have encountered therapeutic failure. Hence, there is a constant need for new best in class or first in class antiviral molecules. We have previously shown that nitrocorroles could be used as a potent anti-hCMV agent without acute toxicity in mice. They therefore represent an excellent platform to perform structure–activity relationship (SAR) studies and to increase efficiency or reduce toxicity. We have generated original A2 B- and A3 -substituted nitrocorroles and have discovered optimized compounds with selectivity indices above 200. These compounds are easily synthesized in only one to two-step reactions; they are up-scalable and cost efficient. They are therefore excellent candidates for hCMV therapies and they pave the way for a new generation of molecules.